Pure species discriminate against hybrids in the Drosophila melanogaster species subgroup. (1st July 2021) - Serrato‐Capuchina, Antonio; Schwochert, Timothy D.; Zhang, Stephania; Roy, Baylee; Peede, David; Koppelman, Caleigh; Matute, Daniel R.
Abstract: Introgression, the exchange of alleles between species, is a common event in nature. This transfer of alleles between species must happen through fertile hybrids. Characterizing the traits that cause defects in hybrids illuminates how and when gene flow is expected to occur. Inviability and sterility are extreme examples of fitness reductions but are not the only type of defects in hybrids. Some traits specific to hybrids are more subtle but are important to determine their fitness. In this report, we study whether F1 hybrids between two species pairs of Drosophila are as attractive as the parental species. We find that in both species pairs, the sexual attractiveness of the F1 hybrids is reduced and that pure species discriminate strongly against them. We also find that the cuticular hydrocarbon (CHC) profile of the female hybrids is intermediate between the parental species. Perfuming experiments show that modifying the CHC profile of the female hybrids to resemble pure species improves their chances of mating. Our results show that behavioral discrimination against hybrids might be an important component of the persistence of species that can hybridize.